Density Gradient Separation of Human Platelets from Plasma and the Role of Plasma in Adenosine Diphosphate Induced Platelet Electrophoretic Mobility Changes - Nicholls, D. G; Hampton, J. R (Thrombosis and Haemostasis, 1972)
1. An albumin density gradient separation technique is described for separating human blood platelets from plasma.2. The platelet resuspensions aggregate on the addition of 10-6 M adenosine diphosphate (ADP) in the presence of calcium and fibrinogen.3. Platelet resuspension in the presence of plasma show a time dependant recovery of reversible aggregation.4. In the presence of calcium and fibrinogen platelet resuspensions show ADP- induced electrophoretic mobility changes which are the same as those of platelets not separated from their native plasma.5. Abnormal electrophoretic sensitivity to ADP in platelets from subjects with a history of occlusive arterial disease is retained on separation from plasma.6. The electrophoretic response of platelet resuspensions to phosphatidyl choline is similar to that of unwashed platelets. The use of resuspended platelets has shown that calcium and fibrinogen are not required for this response.